If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -28 = 14u Solving -28 = 14u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-14u' to each side of the equation. -28 + -14u = 14u + -14u Combine like terms: 14u + -14u = 0 -28 + -14u = 0 Add '28' to each side of the equation. -28 + 28 + -14u = 0 + 28 Combine like terms: -28 + 28 = 0 0 + -14u = 0 + 28 -14u = 0 + 28 Combine like terms: 0 + 28 = 28 -14u = 28 Divide each side by '-14'. u = -2 Simplifying u = -2
| -m-3m=16 | | (3x-11)/8=x | | 72=(x-1)(x)(x+9) | | 7X+5.5Y=119 | | sqrt-7x+5=sqrt-3x+9 | | 3n-6n=-15 | | 4y-13= | | 4y+38=20+8y | | 2(x+15)=x+21 | | y(49/60)=(7/2) | | x+15=x+21 | | =ln(0.5x^2) | | ((x^2)+y)dx=-xdy | | 6(2n-2)=(8n+8)+1 | | a=1/2bc2 | | (5x-14)+90+y=180 | | 3n-1=-28 | | 4a+8=2a | | 5m-1=14 | | 5L-12=38 | | (2x+13)+3x+57=180 | | -k+5=24 | | -8j-59=13 | | 5*x+57= | | 14i-5=-33 | | 14I-5=-93 | | 3(x-2)+2x=7-(x+5) | | (2c-3)(2c+4)(2c-1)=0 | | 70=(x*x+2*2) | | -12g-4=44 | | -10m+8=-8 | | (x^2+9x+4)=0 |